Association of Fibrosing Myopathy in Systemic Sclerosis and Higher Mortality. Issue 11 (27th October 2017) - Paik, Julie J.; Wigley, Fredrick M.; Shah, Ami A.; Corse, Andrea M.; Casciola‐Rosen, Livia; Hummers, Laura K.; Mammen, Andrew L.
Abstract : Objective: To determine if a unique subtype of scleroderma muscle disease exists by comparing the clinical features of systemic sclerosis (SSc; scleroderma) patients with predominant fibrosis on muscle biopsy to those with inflammatory muscle histopathology. Methods: This retrospective, cross‐sectional study included SSc patients with muscle weakness and an available muscle biopsy. Biopsies with fibrosis but without inflammation/necrosis were designated as "fibrosing myopathy, " and those with inflammation and/or necrosis were assigned a category of "inflammatory myopathy." Clinical data, including features of SSc, serum creatine kinase (CK) levels, electromyography, autoantibody profile, and survival, were compared between the 2 groups. Results: The study population consisted of 37 weak SSc patients, 8 with fibrosing myopathy and 29 with inflammatory myopathy. Compared to those with inflammatory myopathy, patients with fibrosing myopathy were more likely to have diffuse SSc skin subtype (87% versus 62%; P = 0.18), African American race (62.5% versus 37.9%; P = 0.20), and a lower mean ± SD forced vital capacity (55.5 ± 31.9 versus 66.4 ± 17.6; P = 0.23). They also had lower mean ± SD CK values (516 ± 391 versus 2, 477 ± 3, 511 IU/liter; P = 0.007) and lower aldolase values (13.8 ± 4.7 versus 27.3 ± 4.7; P = 0.01). Patients with fibrosing myopathy had a significantly higher mortality (5 of 8 [62.5%] versus 4 of 29 [14.3%]; P = 0.005). Conclusion: Fibrosing myopathy is a unique histologic subtype of muscle disease among weak patients with SSc and is associated with significantly worse mortality compared to those with inflammation and/or necrosis on muscle biopsy.